Usinas hidrelétricas: a percepção dos gestores sobre as contribuições da divulgação voluntária para legitimidade organizacional - Voltarelli, Francielle Rodrigues (2018)
The issue of legitimacy is a relevant theme in organizational studies, which has been referenced in the literature and widely discussed in the organizational context. Several studies indicate that one of the ways to legitimize organizations used is the voluntary disclosure of information, and this disclosure may be due to several factors. In the model of Suchman (1995), voluntary disclosure of information can contribute strategically as an instrument for organizations to gain, maintain or recover legitimacy in a pragmatic, moral or cognitive way. In this context, this research was carried out with the objective of analyzing how the voluntary disclosure of information about the natural environment contributes to the organizational legitimacy of hydroelectric plants. Regarding the methodological course of the research, regarding the problem, it is classified as qualitative; as to the objective, carried out a qualitative study, through the study of multiple cases, in which documentary data and interviews were analyzed. The first stage of the study consisted of documentary research, in which the sustainability reports produced by the companies that operated the hydroelectric plants in the state of Paraná were analyzed. In the second stage, interviews were conducted with managers of these operating companies, who participate in the elaboration of the sustainability report, seeking to understand the contributions perceived by them through the use of voluntary disclosure of information about the natural environment. The results demonstrate that the discourses about the natural environment contained in the analyzed sustainability reports are also those perceived as a contribution when divulged by the managers interviewed. The predominant purpose both in the speeches of the report and in the interviewees' perception was to gain legitimacy, being used in balance in the pragmatic, moral and cognitive categories. It can be concluded that the dissemination of voluntary information on the natural environment contributes to the organizations obtaining a state of legitimacy, mainly through the use of strategies aimed at gaining legitimacy. It was also identified that some disclosures, however perceived by the respondents as contributions, are sometimes only punctuated or are not always disclosed, due to the care with the extension of the report or for fear of exposing strong partners involved. These findings make it easy for developers and stakeholders to understand that not all information will be clearly detailed and that they may opt for other channels of voluntary communication of information on the natural environment.